A new drug triggering mechanism in thermosensitive nanoparticles using a low-melting-point polymer / Ali Dabbagh - Ali, Dabbagh (2016)
Thermosensitive nanocarriers are increasingly used to allow time and site-specific drug release with minimized systemic toxicity. Thermal-triggered drug release is often governed by coil-globule, membrane disruption, and micellization mechanisms. However, premature and slow drug release, low stability, and insufficient bioavailability remain challenging in most nanocarriers which utilize these triggering mechanisms. This work aimed to introduce a new triggering mechanism using polymers with gel-liquid phase transition at hyperthermia and thermal ablation temperatures. This phase transition could generate structural defects in nanocarriers and thus facilitate drug release. In addition, for accurate assessment of the heated region during in vitro evaluation of nanocarriers, a novel thermosensitive phantom was developed. Nanocarriers were synthesized using mesoporous silica nanoparticles (MSNs) as drug reservoir and two polymer formulations including polyacrylamide (PAA) and polyethylene glycol (PEG) as the protective nanoshells. The graft-from and graft-to techniques were respectively employed to prepare PAA-MSNs and PEG-MSNs. The phase transition behaviours as well as various chemical, morphological, and thermal properties of these nanocarriers were characterized and their drug loading and release potentials were investigated using doxorubicin as a hydrophilic model drug. Magnetic resonance-guided focused ultrasound (MRgFUS) was also employed as a typical thermal modality to evaluate the drug release rates in short-term treatment intervals. The required phantom for MRgFUS experiments was developed using a thermochromic dye with reversible discolouration at hyperthermia range. Various physical, thermal, and acoustic properties of this phantom were measured to ensure their proximity to those of human iv soft tissues. The thermosensitive behaviour of this phantom was evaluated using radiofrequency (RF) and MRgFUS experiments. The aqueous solutions containing drug-loaded nanocarriers were further embedded within the phantom and sonicated by MRgFUS to determine their efficacy as adjuvants to this thermal modality. Spectrophotometry analysis of the phantom showed a threshold temperature of 50±3°C with a 6°C difference between the onset and ending discolouration temperatures. The contrast change at focal point during sonication also allowed visualization of the thermal lesion in magnetic resonance images. The onset transition temperatures of PAA-MSNs and PEG-MSNs were 45.1±3.4°C and 40.4±1.8°C, respectively. The peak transition temperature of PEG-MSNs was also 20°C lower than that of PAA-MSNs, resulting in significantly sharper phase transitions. Drug release measurements for PAA-MSNs showed 11.5±2.4% leakage at 37°C after 30 minutes, while this value was significantly increased to 20.2±4.3% in PEG-MSNs. However, the maximum release ratio in PEG-MSNs (68.2±3.7%) was obtained at 50°C which was 10°C lower than that of PAA-MSNs (67.6±2.5% at 60°C). The drug release ratio from PEG-MSNs (45.5±3.1%) under MRgFUS exposure was also significantly higher than PAA-MSNs (39.2±2.2%). Melting of polymer shells at hyperthermia and thermal ablation temperature ranges could provide thermal-triggered drug release from the core-shell nanocarriers with relatively low undesired release at physiological temperature. The drug release ratio from PEG-MSNs at physiological temperatures was higher than PAA-MSNs. However, the maximum drug release in these nanocarriers was obtained in significantly lower temperatures. Both PAA-MSNs and PEG-MSNs exhibited high loading efficiencies and rapid drug release rates at increased temperatures which make them promising for application as adjuvants to thermal modalities.